ANALISIS SISTEM INFORMASI PROSES PRODUKSI INJECTION PHYLON DI PT. CHANG SHIN INDONESIA CIKAMPEK-KARAWANG - DALDIRI (INFOKOM (Informatika & Komputer), 2018)
This study aims to find out how big influence the application of productioninformation system Injection Phylon on productivity, balancing the input and output datain the production process Injection Phylon (IP) at PT. Chang Shin Indonesia IPCikampek.This study takes a sample of the number of Person In Charge (PIC) scannedpoints totaling as many as 19 people.The method used in this research is interviewmethod, document analysis and evaluation method. To know the prevailing informationsystem then do the research by way of observation and inquire through interview withPIC scan as user of system itself which consist of several work unit PT. Chang ShinIndonesia IP-Cikampek.The Application of Information System in PT. Chang Shin Indonesia IPCikampekhas been running very effectively, efficiently and accurately. Where the needsof each Department by staff employees can be easily accessed in accordance with theprocedures by the system.Information Systems in use is the Global ManufacturingExecution System (GMES).And the problems revealed in this study are as follows: 1). Theproblem is that PIC sometimes does not perform barcode scan according to SOP. Thereare still unequal data input and output due to Batchcard or Passcardsering dropped, losteven broken. Suggestion: re-socialize the importance of the scanning process so that theemployee's mindset changes for the better. Create a missing and damaged Batchcard /Passcard SOP. 2). There is still a disruption of server connection on the shift that worksnight, the system sometimes does not work. Suggestion: IT team can review the problemand immediately improve the broken connection.